ANALISIS KINERJA SIMPANG BERSINYAL DENGAN MENGGUNAKAN PROGRAM SYNCHRO (STUDI KASUS PADA SIMPANG JL. MAJAPAHIT – JL. FATMAWATI DAN JL. MAJAPAHIT – JL. SOEKARNO HATTA, SEMARANG) - Nolo Paramarto; Priyo Hartono; Ismiyati Ismiyati; Bagus Hario Setiadji (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Majapahit road is one of important roads in Semarang city which is the entrance to the city from the East bound. There are adjacent intersections on this road with distance only 70 m, namely Jalan Majapahit - Jalan Fatmawati intersection and Jalan Majapahit - Jalan Soekarno Hatta intersection. This adjacent intersections have been causing long delay and high degree of saturation, especially at morning- and afternoon-peak hours . This study aims to analyze the performance of the intersections, and to provide recommendations to improve the traffic performance by applying various scenarios using Synchro plus SimTraffic 7.0 program. The scenario proposed were conducting traffic management, widening the road, and so on.To ensure that Synchro program can be used in the simulation, validation of the Synchro’s results was performed by comparing them with those of Manual Kapasitas Jalan Indonesia (MKJI) 1997. The analysis produced that at this moment, the intersectionscannot serve well the flow of traffic, as shown by the degree of saturation of the intersections that exceeded 0,75.Several scenarios have been made to solve the problem of congestion at intersections and the among them, traffic management is the best one that could be recommended.However, the implementation of the scenario needs the local government to play the role in issuing regulations which could reduce the volume of vehicles passing through the intersections such as increasing public transpor contribution, imposing three-in-one systems, electronic road pricing system, or as well as other policies.